Introduction to the urban ecologies open collection: A call for contributions on methods, ethics, and design in geographical research with urban animals. Issue 2 (28th September 2021) - Oliver, Catherine; Ragavan, Shruti; Turnbull, Jonathon; Chowdhury, Anmol; Borden, Diane; Fry, Thomas; Gutgutia, Sneha; Srivastava, Shubhangi
Abstract: This Open Collection proposes innovative research directions for both urban and beyond/more‐than‐/non‐human geographies with animals. We are seeking papers for this Open Collection across three themes: (1) methods; (2) ethics and politics; and (3) planning and design. Specifically, we are interested in papers that pose questions of and reflect upon emergent tensions in researching with urban animals in each of these themes. This Open Collection aims to explore urban space beyond the human lens and to offer new modalities and frameworks for geographical research with urban animals. We are interested in papers that explore urban geographies with animals from a range of different theoretical, methodological, and empirical locations and perspectives. In this introduction to the Open Collection, we briefly summarise existing research in this field, before outlining the three thematic areas of the Collection. Abstract : This Open Collection on "urban ecologies" proposes innovative research directions for both urban and beyond‐/more‐than‐/non‐human geographies, broadly construed. We are seeking papers for this Open Collection across three themes: (1) methods; (2) ethics and politics; and (3) planning and design.